The Concept of Had Kifayah in Zakah Management - Nurizal Ismail; Siti Aisyah (Al Tijarah, 2019)
This research attempts to find the concept of had kifayah (the sufficiency line) in classical Islamic texts (turasts) written by Muslim scholars and to be analysed it in the contemporary relevance of zakah management. It employs a qualitative method by exploring the concept of had kifayah of early Muslim Scholars and analyzing its relevance in the current condition. Moreover, the findings are clearly stated that the concept of had kifayah is derived from the works of early Muslim scholars that gives a fundamental philosophical framework toward the development of had kifayah study in zakah management.The existing research covers the study of had kifayah focusing on formulating the measurement of had kifayah with some additional Islamic values that based on the maqasid Shari’ah approach. However, the comprehensive study on the had kifayah based in Islamic perspective has been not executed very much in this regard. This research will contribute to the development of Islamic economics because the concept had kifayah related to the development of zakah management